One‐Pot Synthesis of 2‐Amino‐6‐(1, 2‐dihydro‐4‐hydroxy‐2‐oxoquinolin‐3‐yl)‐4‐arylpyridine‐3‐carbonitriles Catalysed by NbCl5 and Their In Vitro Antimicrobial Studies. Issue 34 (9th September 2019) - Krishna, Alla.; Sarveswari, S.
Abstract: Synthesis of 2‐amino‐6‐(1, 2‐dihydro‐4‐hydroxy‐2‐oxoquinolin‐3‐yl)‐4‐arylpyridine‐3‐carbonitrile has been accomplished via NbCl5 catalysed multicomponent reaction (MCR). The tested compounds showed better potency than Neomycin and a broad spectrum of antibacterial activity against Staphylococcus aureus, Bacillus cereus and Escherichia coli. Similarly some of these have showed good activity against Staphylococcus aureus, Klebsiella planticola and Escherichia coli that were comparable to Ciprofloxacin. Also these compounds possess good antifungal activity that was better than Miconazole and comparable to Ciprofloxacin hydrochloride. Abstract : One‐pot synthesis of quinolone based 2‐amino‐3‐cyano pyridine derivatives has been accomplished by NbCl5 catalysed multicomponent reaction (MCR). Potential antibacterial activity by these newer quinolones against Staphylococcus aureus, Bacillus cereus, Escherichia coli and Klebsiella planticola has been described. Good antifungal activity by these derivatives has also been documented.